KESETARAAN MENURUT BERBAGAI AGAMA: Perspektif Islam, Kristen, dan Hindu - Fajar, Muhammad Brilian (AKADEMIK: Jurnal Mahasiswa Humanis, 2023)
Gender equality is a deep and complex issue in today's global society. The concept of gender equality is interpreted in various ways, including in various religions that have a significant influence on the lives of individuals and society. Islam, Christianity and Hinduism are the three main religions that have millions of followers around the world. Therefore, this research aims to analyze and understand views on gender equality in these three religions with the hope of providing deeper insight into the relationship between religions and gender issues. The research method used is in-depth text analysis, by identifying key texts related to gender equality in the three religions. The results of this study reveal significant differences in views about gender equality in Islam, Christianity, and Hinduism. Islam emphasizes equality in its basic teachings, with an emphasis on justice and equal treatment before Allah. Christianity has a variety of different interpretations of gender equality, but a growing number of denominations support gender equality in church and family roles. Hinduism, as a diverse and pluralistic religion, has a variety of views influenced by different traditions and sects.